PUBLIC RELATIONS PADA PENGASUH YAYASAN MUKTAR SYAFA’AT BLOKAGUNG BANYUWANGI - umam, khotibul; aziz, abdul; maksunah, Unstiati (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2024)
The leadership of a female nanny, is a public figure in a public relationship with the leadership of the Islamic boarding school, and influences the development of the students at the Islamic boarding school. The purpose of this study was to determine Analyzing the leadership of female caregivers in cultivating public relations for students at the Mukhtar Syafa'at Islamic Boarding School. Knowing the leadership strategy of female caregivers in growing public relations for students at the Mukhtar Syafa'at Islamic boarding school. In this study, the research method used is a qualitative approach using descriptive research. The results of this study indicate that the pattern of nannying the daughter of Mrs. Nyai Hj Mahmudah Ahmad S.Sos.I, M.Pd.I is in fostering public relations for the students of the Mukhtar Syafa'at Islamic boarding school. Among them, namely the first is the leadership of a female nanny applying positive behavior including motivating the students, setting a good example, giving advice at certain times especially when it is needed, encouraging students to become enthusiastic people, studying seriously, cultivating good communication. The two techniques used by Mrs. Nyai Mahmudah Ahmad S.Sos.I, M.Pd.I set a good example and role model for the students, and were also firm in conveying everything and respecting the opinions of others.